2016
DOI: 10.1142/s2424835516500090
|View full text |Cite
|
Sign up to set email alerts
|

The Anatomical Relationship Between the Dorsal Cutaneous Branch of the Ulnar Nerve and the Ulnar Styloid Process with Variations in Forearm Position

Abstract: We recommend making a skin incision on the ulnar side around the styloid process with the forearm in supination or neutral position was another method to avoid injury of DCBUN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…The DBUN crossed the ulna at a mean distance of 1.4 cm (range 0.6–2.5) proximal to the US (Le Corroller, 2013), and Uerpairojkit et al (2019) found the DBUN crossed the vertical axis through the US a median of 1.0 cm distal to the US and 14% crossed at the level of the tip of the US. Jung et al (2016) also found the DBUN crossed the ulna distal to the US and moved closer to the US in an ulnar‐radial direction with a forearm position change from supination to pronation.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…The DBUN crossed the ulna at a mean distance of 1.4 cm (range 0.6–2.5) proximal to the US (Le Corroller, 2013), and Uerpairojkit et al (2019) found the DBUN crossed the vertical axis through the US a median of 1.0 cm distal to the US and 14% crossed at the level of the tip of the US. Jung et al (2016) also found the DBUN crossed the ulna distal to the US and moved closer to the US in an ulnar‐radial direction with a forearm position change from supination to pronation.…”
Section: Resultsmentioning
confidence: 93%
“…The origin of the dorsal branch of the ulnar nerve (DBUN) from the ulnar nerve remained consistent in all studies, including in vivo, cadaveric studies, and ultrasound. Uerpairojkit et al (2019), Jung et al (2016), and Root et al (2013) noted that the DBUN originated 6.8, 4.92, and 5.1 cm proximal to the tip of the US, respectively, in cadaveric studies (Figure 2). In ultrasound studies on cadavers, Sulaiman et al (2013) noted that the DBUN originated 6.97 ± 2.39 cm proximal to the US.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations